Cultural conceptions of mental health and therapy. - White, Geoffrey M.; Marsella, Anthony J. (Dordrecht : D. Reidel, 1989)
Introduction / White, G.M. ; Marsella, A. J. -- Culture and Psychiatric Illness / Fabrega, H.jr -- The Ethnographic Study of Cultural Knowledge of "Mental Disorder" / White, G.M. -- Does the Concept of the Person Vary Cross-culturally? / Shweder, R.A. ; Bourne, E. J. -- Toward a Meaning-centered Analysis of Popular Illness Categories / Good, B. J. ; Delvecchio Good, M. -- Cultural Definitions / Gaines, A. D. -- Samoan Folk Knowledge of Mental Disorders / Clement, D. C. -- Popular Conceptions of Mental Health in Japan / Lock, M. -- Science and Psychological Medicine in the Ayurvedic Tradition / Obeyesekere, G. -- The Unbounded Self / Connor, L. -- Self-Reconstruction in Japanese Religious Psychotherapy / Lebra, T. S. -- Psychoterapy and Emotion in Traditional Chinese Medicine / Wu, D. Y. H. -- Shaman-Client Interchange in Okinawa / Lebra, W.P. -- Sunao : A central value in Japansese psychotherapy / Murase, T. -- The Intercultural Context of Counseling and therapy / Pedersen, P. -- Culture and Mental Health / Marsella, A.J.
Notes. Bibliogr. dissém. Index.